Sales promotion practice in Metro Manila for year 2001 Splash Corporation beauty care specifically it's major products soap, astringent, cologne : an evaluation - Galban, Eloisa M. (Manila: National University, 2003)
This study is concerned with the sales promotion activities of a beauty care products in Splash.
Title page -- Approval Sheet -- Dedication -- Acknowledgement -- Table of Contents -- List of Tables -- Chapter 1. Introduction and Background of the Problem -- Chapter 2. Study of Related Literature -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis, and Interpretation -- Chapter 5. Summary of Findings, Conclusions, and Recommendations -- Appendix.
Research Method : Descriptive Survey Research Design
Includes bibliographical references.